TALENT MANAGEMENT STRATEGIES OF MULTINATIONAL CORPORATIONS: ADAPTATIONS IN EMERGING ECONOMIES - Mohanty, Dr. Sasmita; Pattnaik, Manaswini (The journal of contemporary issues in business and government, 2021)
The strategic significance of talent management is increasing specifically in the emerging economies owing to their demographic dividend. Since the emerging economies have come to the forefront due to their participation in global knowledge economy, it is essential to revisit their human capital development and talent management particularly when dealt by the large MNCs of the world. Researches on talent management strategies have largely focused on the large developed economies and the practices thereof have been replicated in the rest of the world without much deliberation on their efficacy. This paper has three principal objectives: one to explore the factors that have led to the focus of talent management practitioners on emerging countries, two to explore the talent management practices of multinational corporations in their extensions located at emerging economies and finally after analysing the institutional norms in local subsidiaries of these MNCs, to find out strategies for translating the global strategies into local and provincial cases.